Relationships Between Depressive Symptoms, Dietary Inflammatory Potential, and Sarcopenia: Mediation Analyses - Chen, Guo-Qiang; Wang, Gang-Pu; Lian, Ying (Frontiers in Nutrition, 2022)
Background: Sarcopenia is a major public health problem. Depressive symptoms and dietary inflammatory potential play important role in the development of sarcopenia. We aimed to disentangle the relationships between depressive symptoms, dietary inflammatory potential, and sarcopenia. Methods: A total of 6082 participants from the National Health and Nutrition Examination Survey were included in the analyses. Sarcopenia was defined according to the Foundation for the National Institutes for Health criteria. Depressive symptoms were assessed using the nine-item Patient Health Questionnaire. Dietary inflammatory index (DII) was calculated based on two 24-hour dietary recall interviews. Two sets of mediation models were constructed separately. Results: Depressive symptoms and DII were associated with sarcopenia, with ORs (95%CIs) 2.54 (1.27, 5.13) and 1.17 (1.00, 1.37), respectively. DII score mediated the association of depressive symptoms with low muscle mass, explaining a total of 10.53% of the association (indirect effect: β = 0.007). Depressive symptoms had a significant mediating effect on the association between DII with low muscle mass, explaining a total of 12.50% of the association (indirect effect: β = 0.04). Conclusions: Our findings suggested that both depressive symptoms and dietary inflammatory potential had direct effects, and indirect effects on low muscle mass, handgrip strength, muscle mass, through each other. It provides important insights into integrated nutritional and psychological intervention strategies in preventing sarcopenia.